Visually tracked flashlights as interaction devices - Green, Jonathan (2008)
This thesis examines the feasibility, development and deployment of visually tracked flashlights as interaction devices. Flashlights are cheap, robust and fun. Most people from adults to children of an early age are familiar with flashlights and can use them to search for, select and illuminate objects and features of interest. Flashlights are available in many shapes, sizes, weights and mountings. Flashlights are particularly appropriate to situations where visitors explore dark places such as the caves, tunnels, cellars and dungeons that can be found in museums, theme parks and other visitor attractions.